Synthesis of Some Novel Substituted Arylidene and Substituted Benzylthiazolidine-2,4-dione Analouges as Chemotherapeutic Agents - Malik, Sachin; Choudhary, Ashish; Shyam Bahare, Radhe (Asian Journal of Chemistry, 2011)
A series of 5-substituted arylidene and 3-substituted benzylthiazolidine-2,4-dione derivatives were synthesized from thiazolidinedione and substituted benzyl chloride followed by the addition of substituted aromatic aldehydes. All the compounds 1a-e and 2a-c were screened for their in vitro antimicrobial activity using cup plate method.